Phosphatidylinositol 4,5-bisphosphate is regenerated by speeding of the PI 4-kinase pathway during long PLC activation - Myeong, Jongyun; de la Cruz, Lizbeth; Jung, Seung-Ryoung; Yeon, Jun-Hee; Suh, Byung-Chang; Koh, Duk-Su; Hille, Bertil (The Journal of general physiology, 2020)
The dynamic metabolism of membrane phosphoinositide lipids involves several cellular compartments including the ER, Golgi, and plasma membrane. There are cycles of phosphorylation and dephosphorylation and of synthesis, transfer, and breakdown. The simplified phosphoinositide cycle comprises synthesis of phosphatidylinositol in the ER, transport, and phosphorylation in the Golgi and plasma membranes to generate phosphatidylinositol 4,5-bisphosphate, followed by receptor-stimulated hydrolysis in the plasma membrane and return of the components to the ER for reassembly. Using probes for specific lipid species, we have followed and analyzed the kinetics of several of these events during stimulation of M1 muscarinic receptors coupled to the G-protein Gq. We show that during long continued agonist action, polyphosphorylated inositol lipids are initially depleted but then regenerate while agonist is still present. Experiments and kinetic modeling reveal that the regeneration results from gradual but massive up-regulation of PI 4-kinase pathways rather than from desensitization of receptors. Golgi pools of phosphatidylinositol 4-phosphate and the lipid kinase PI4KIIIα (PI4KA) contribute to this homeostatic regeneration. This powerful acceleration, which may be at the level of enzyme activity or of precursor and product delivery, reveals strong regulatory controls in the phosphoinositide cycle.The dynamic metabolism of membrane phosphoinositide lipids involves several cellular compartments including the ER, Golgi, and plasma membrane. There are cycles of phosphorylation and dephosphorylation and of synthesis, transfer, and breakdown. The simplified phosphoinositide cycle comprises synthesis of phosphatidylinositol in the ER, transport, and phosphorylation in the Golgi and plasma membranes to generate phosphatidylinositol 4,5-bisphosphate, followed by receptor-stimulated hydrolysis in the plasma membrane and return of the components to the ER for reassembly. Using probes for specific lipid species, we have followed and analyzed the kinetics of several of these events during stimulation of M1 muscarinic receptors coupled to the G-protein Gq. We show that during long continued agonist action, polyphosphorylated inositol lipids are initially depleted but then regenerate while agonist is still present. Experiments and kinetic modeling reveal that the regeneration results from gradual but massive up-regulation of PI 4-kinase pathways rather than from desensitization of receptors. Golgi pools of phosphatidylinositol 4-phosphate and the lipid kinase PI4KIIIα (PI4KA) contribute to this homeostatic regeneration. This powerful acceleration, which may be at the level of enzyme activity or of precursor and product delivery, reveals strong regulatory controls in the phosphoinositide cycle.